Abdulla Avlani and the National Independence Movement - Juraev Oybek (Researchparks Publishing, 2022)
This article talks about the activities of representatives of the Uzbek jaded movement, and the role of Abdulla Avlani in this process, and his contribution to the jaded movement. Abdulla Avlani's activity is revealed through the biographical method.